Degenerated nerve grafts provide similar quality and outcome in reconstructing critical nerve defects as compared to fresh nerve grafts - Tratnig-Frankl, Philipp; Schmoll, Martin; Maierhofer, Udo; Klepetko, Johanna; Jaklin, Florian J.; Jöns, Lisa H.; Zirak, Homayon; Festin, Christopher; Harnoncourt, Leopold; Tereshenko, Vlad; Bergmeister, Konstantin D.; Aszmann, Oskar C. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionBrachial plexus injuries are commonly caused by stretch-traction injuries. The clinical standard is timely anatomic reconstruction with autologous nerve grafts and/or intra- or extraplexal nerve transfers. Commonly used nerve grafts are the sural nerves and/or grafts taken from the affected side. If the lower trunk has been affected, the latter nerves, however, are predegenerated. In this animal experiment we investigated, whether a degenerated nerve graft avails the same quality of regeneration as compared to a non-degenerated graft.Methods and materialsIn this animal study, a 2 cm lesion of the right common peroneal nerve was created, and the ipsilateral sural nerve was cut or left intact to later serve as a graft. Nerve reconstruction was carried out 3 weeks later using the fresh or degenerated graft. After 6 weeks, either a retrograde labeling of the common peroneal nerve or muscle force testing was performed.ResultsA total of 34 male SD rats, Group A (n = 13) and Group B (n = 21) were included. In Group A, the retrograde labeling of the spinal motor neurons showed an average of 66.05 (±17.03) neurons in animals with a fresh graft and 41.19 (±10.47) neurons in animals with a degenerated graft. In two animals with a fresh graft, no motor neurons could be labeled. No statistical inferiority was observed (p = 0.071). In Group B, regeneration is expressed as a recovery ratio. The fresh graft group had a mean maximum evoked contraction of 8.2 (±7.1), compared to 8.5 (±4.9) in the degenerated graft group (p = 0.462). The mean maximum twitch force was 5.2 (±3.5) and 6.4 (±4.4) respectively (p = 0.577). The mean muscle weight, comparing injured to uninjured side, was 0.32 (±0.06) in the fresh graft group and 0.32 (±0.04) in the degenerated graft group (p = 0.964).ConclusionThe use of predegenerated nerve grafts for critical nerve reconstruction showed no statistical inferiority as compared to the fresh grafts in any of the evaluated outcome. Overall, these results are promising, particularly in the context of critical nerve defects involving multiple nerves, where the use of a degenerated grafts often remains the only additional source of graft material.